From Use to Design: Rethinking Urban Furniture for Sustainable Urban Spaces (Case of Plazas in Batna) - CHETARA Aïcha; FENGHOUR Abir (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Urban furniture, long relegated to a purely decorative role, is now recognized as a crucial component in the design of public spaces. In Algeria, it often remains poorly adapted to local socio-economic and environmental realities. This research focuses on analyzing the impact of urban furniture on the plazas in Batna, assessing its role in transforming these spaces into sustainable and functional areas. The aim is to demonstrate that urban furniture design, far from being incidental, profoundly influences key factors such as comfort, safety, utility, and the aesthetics of public spaces. By reflecting on the adaptability of urban furniture elements, we highlight their fundamental contribution to sustainable urban planning. This study underscores the importance of thoughtful, adaptive, and intelligent furniture in creating more resilient, pleasant, and genuinely functional cities, aligned with the needs of users and contemporary environmental challenges.